Dermatophytosis a worldwide contiguous fungal infection: Growing challenge and few solutions - Falah Hasan Obayes AL-Khikani (Biomedical and Biotechnology Research Journal, 2020)
Dermatophytes are filamentous fungi that survive on keratinous materials. There is a broad prevalence of dermatophytes infection among the world. Dermatophytosis is the disease that mainly caused by different species of dermatophytes within the cutaneous layer of the skin. It has contagious properties to spread from person to another and also from the animal to the human. The skin, hair, and nail of all types of mammalian, including human, are under the risk to develop dermatophytosis. A total of 2530 articles have been investigated in PubMed (n = 1525), Medline (n = 705), and Google Scholar (n = 300). From 2530 articles, just 48 studies were included in this review. This study aimed to review available data and current literature as well as information from personal experiments regarding dermatophytes infection to focus on the dermatophytes general features, dermatophytosis, pathogenesis presented by enzymes production, most common factors associated with infection, prevalence, and treatment of dermatophytes infection, and also to yield a clear vision to other researches about this worldwide predominant contiguous fungal disease.